(untitled) (Confluenţe Bibliologice, 2026)
This article reflects on the life and work of Priest Vasile Secrieru, born into a large and modest family. After studying history in Romania, he worked as a teacher and librarian before, under the guidance of Priest Valeriu Cernei in Bălți, choosing the path of priesthood. He served as deacon and priest in Sloveanca (Sângerei), Buzdugeni (Edineț), and since 2007 in Găvănoasa (Cahul), dedicating himself to church restoration, supporting parishioners, catechesis, and community development. Despite facing numerous challenges and trials, he maintained faith and devotion, contributing to the founding of a monastery and supporting multiple families, serving selflessly alongside his wife and five children.